KONTRIBUSI DANA PIHAK KETIGA TERHADAP RENTABILITAS EKONOMIS (STUDI KASUS DI PT BANK MUAMALAT INDONESIA) - Agung Budi (Universitas Muhammadiyah Tangerang, 2017)
This research aims to figure out how significant is the effect of The Third Party Funds (the research focuses on the Deposit of Mudharabah, Mudharabah Savings, and the Wadi’ah Giro) towards Economical Profitability at PT. Bank Mu’amalat Indonesia (BMI). This research is a kind of a descriptive research through correlational regression method. It aims to figure out how significant is one or more than one variables may give the influence towards other variables. The result of this research shows that The Third Funds does not have any significant effect towards the Economical Profitability with the gained correlational value 31,4%. It goes without saying, 68,6% of Economical Profitability is influenced by other variables which are not identified in this research.Kata Kunci : Third Fund Party, Economic Rentability